The Role of Informal Lending Practices in Supporting Microenterprise Development: A Case Study of Molompar Village, Southeast Minahasa - Kamah, Irma Sari (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2024)
This study explores the dynamics of informal lending practices in Molompar Village, Southeast Minahasa, Indonesia, and their role in supporting microenterprise development. Informal lending has become a lifeline for microentrepreneurs who face barriers such as limited access to formal financial institutions due to stringent requirements, including collateral and complex documentation. Through qualitative methods, including observations, interviews with three informal lenders and five borrowers, and document analysis, the study identifies key drivers behind the reliance on informal loans, including their accessibility and flexibility. The findings reveal that while informal lending enables microentrepreneurs to expand their operations, increase inventory, and stabilize income, it also imposes significant challenges. High interest rates, the absence of legal protections, and social stigma associated with delayed repayments create financial and social vulnerabilities for borrowers. Despite these drawbacks, informal lending plays a critical role in filling the financial gap left by formal institutions, fostering entrepreneurship and local economic growth. The study highlights the need for integrating informal lending into formal financial systems to ensure equitable access and borrower protection. Recommendations include adopting microfinance models that retain the flexibility of informal lending while reducing risks for borrowers. Limitations of the study include its focus on a single village, suggesting the need for broader regional research.